(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The study aims to determine the distribution of the ABO/Rhesus Blood Groups among Hepatitis B virus (HBV) positive patients in Lagos State. Copies of structured questionnaires were distributed to 162 HBV patients that visited selected health facilities within 6 months in the city. After obtaining relevant information, whole blood samples were collected from each participant in an EDTA bottle. Thereafter, the ABO blood group types (A, B, AB, and O) as well as Rhesus blood groups were determined using standard protocols. Results showed that 48.1% of the participants had type O blood group, followed by type A (26.5%), type B (24.7%), and type AB (0.6%). Moreover, 94.4% of the participants were Rh+. The study showed that HBV was more prevalent among participants with type O blood group (48.1%) with rhesus positivity of 94.4%, compared to other blood group types. This indicates that type O individuals in the city could be more susceptible to HBV infection. There should be public awareness on the association between ABO/Rh blood groups and the prevalence of HBV infection in the state.